SISTEM INFORMASI GEOGRAFIS PENENTUAN RUTE EVAKUASI KAWASAN RAWAN BANJIR DI KABUPATEN KUDUS - Caroline, Dyta; Pinem, Agusta Praba Ristadi (J SIG (Jurnal Sains Informasi Geografi), 2024)
At the beginning of 2023, several regions in Indonesia, such as Kudus Regency in Central Java, experienced flooding disasters that resulted in the disruption of several inter-district road accesses and had material and immaterial impacts. Based on the disaster infographics data of Kudus Regency, it was recorded that there were 17 flood disaster incidents throughout the year 2022. Sixteen villages were affected by flood disasters spread across three sub-districts, namely Jati, Undaan, and Mejobo, with a total loss of Rp 20,000,000. In 2023, the Regional Disaster Management Agency (BPBD) of Kudus Regency stated that the flooding in Kudus was the most severe compared to the previous year. This was due to high rainfall (>3000 mm) with a relatively flat topography (0-8%). Disaster mitigation procedures have been carried out by the local government in collaboration with the surrounding community to reduce the severity of the incidents. However, the unpredictability of flood disasters due to changing weather and environmental influences each year necessitates further analysis of flood-prone areas and appropriate evacuation procedures. This research is conducted by mapping flood-prone areas using the Scoring and Overlay Data methods, as well as calculating evacuation routes using the Network Analyst method. This analysis utilizes tools available in ArcGIS Desktop software. The selection of appropriate parameters is crucial for more accurate calculations.